Perceived Stress, Psychological Flexibility, and Life Satisfaction in Cancer Patients - Amanat, Samra (Pakistan Journal of Positive Psychology, 2025)
To a majority of individuals, cancer is a life-changing experience. To many, it may be a chance to get new priorities and reduce the number of regrets. A number of side effects, such as pain, nausea, exhaustion, or the cancer or the treatment, may cause dyspnea. In this study, the authors depict the interaction of life satisfaction, psychological adaptability, and perceived stress of cancer patients. Cancer diagnosis and treatment often cause higher stress levels, which affect the psychological health of patients and their overall quality of life. So, in this research, the survey research design was used. The sample size was 130 cancer patients, 65 of whom were male and 65 of whom were female and above 18 years. It used three tests, including the Perceived Stress Scale (Reis et al., 2010), the Acceptance and Action Questionnaire-II (Bond et al., 2011), and the Satisfaction with Life Scale (Diener et al., 1985). The results indicated that psychological flexibility is significantly related to satisfaction in life and perceived stress among cancer patients. Gender difference did not pose significant statistical differences when it was related to life satisfaction, psychological flexibility, and perceived stress among cancer patients. The findings of this research might be used to develop specific interventions aimed at addressing the specific mental health needs of cancer patients.